Common bile duct stones management: A network meta-analysis - Mohseni, Shahin; Bass, Gary Alan; Forssten, Maximilian Peter; Casas, Isidro Martínez; Martin, Matthew; Davis, Kimberly A; Haut, Elliott R; Sugrue, Michael; Kurihara, Hayato; Sarani, Babak; Cao, Yang; Coimbra, Raul (The journal of trauma and acute care surgery, 2022)
Timely management is critical for treating symptomatic common bile duct (CBD) stones; however, a single optimal management strategy has yet to be defined in the acute care setting. Consequently, this systematic review and network meta-analysis, comparing one-stage (CBD exploration or intraoperative endoscopic retrograde cholangiopancreatography [ERCP] with simultaneous cholecystectomy) and two-stage (precholecystectomy or postcholecystectomy ERCP) procedures, was undertaken with the main outcomes of interest being postprocedural complications and hospital length of stay (LOS). PubMed, SCOPUS, MEDLINE, Embase, and Cochrane Central Register of Controlled Trials were methodically queried for articles from 2010 to 2021. The search terms were a combination of medical subject headings terms and the subsequent terms: gallstone; common bile duct (stone); choledocholithiasis; cholecystitis; endoscopic retrograde cholangiography/ERCP; common bile duct exploration; intraoperative, preoperative, perioperative, and postoperative endoscopic retrograde cholangiography; stone extraction; and one-stage and two-stage procedure. Studies that compared two procedures or more were included, whereas studies not recording complications (bile leak, hemorrhage, pancreatitis, perforation, intra-abdominal infections, and other infections) or LOS were excluded. A network meta-analysis was conducted to compare the four different approaches for managing CBD stones. A total of 16 studies (8,644 participants) addressing the LOS and 41 studies (19,756 participants) addressing postprocedural complications were included in the analysis. The one-stage approaches were associated with a decrease in LOS compared with the two-stage approaches. Common bile duct exploration demonstrated a lower overall risk of complications compared with preoperative ERCP, but there were no differences in the overall risk of complications in the remaining comparisons. However, differences in specific postprocedural complications were detected between the four different approaches managing CBD stones. This network meta-analysis suggests that both laparoscopic CBD exploration and intraoperative ERCP have equally good outcomes and provide a preferable single-anesthesia patient pathway with a shorter overall length of hospital stay compared with the two-stage approaches. Systematic Review/Meta Analysis; Level III.